2012
DOI: 10.1097/aog.0b013e31826579e8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Postoperative Outcomes of Female Genital Fistula Repair Surgery

Abstract: Objective To determine predictors of fistula repair outcomes 3 months postsurgery. Methods We conducted a multicountry prospective cohort study between 2007 and 2010. Outcomes, measured 3 months postsurgery, included fistula closure, and residual incontinence in women with a closed fistula. Potential predictors included patient and fistula characteristics, and context of repair. Multivariable generalized estimating equation models were used to generate adjusted risk ratios (ARR) and 95% confidence intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 17 publications
13
72
4
Order By: Relevance
“…Women with fistulas that involve the urethral closure mechanism are at high risk of post-operative urinary incontinence. (8) To help improve the changes of regaining continence after surgery a pubococcygeal sling or other sling-like techniques (13) are used in all women with a short urethra (approximately ≤2 cm) as a preventative measure. After surgery, women received antibiotics on a case by case basis based on risk factors during surgery or post-operative risk assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women with fistulas that involve the urethral closure mechanism are at high risk of post-operative urinary incontinence. (8) To help improve the changes of regaining continence after surgery a pubococcygeal sling or other sling-like techniques (13) are used in all women with a short urethra (approximately ≤2 cm) as a preventative measure. After surgery, women received antibiotics on a case by case basis based on risk factors during surgery or post-operative risk assessment.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the rural nature of much of Malawi and the fact that the Fistula Care Center draws women from around the East Africa region, women included in this analysis were allowed up to 120 days from time of surgery to return for follow-up. We chose incontinence, rather than fistula closure, as our primary outcome since 20% (8) of women with a successful closure may remain incontinent. (5-7)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, smaller fistula size after prior repair may be one explanation of the comparable success rate on second repair. In a prospective cohort study with 1,274 patients with female genital fistulas, Barone et al [22] found fistula size had no relationship with the successful closure of repair. However, the participants in the study consisted of a heterogeneous population of patients with various genital fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a shortage of reliable data around social, demographic and clinical factors associated with time to recovery from obstetric Fistula surgical repair that will be valuable for managing health care institution through planning, monitoring and evaluation of quality of care as well as use of human and material resources [29][30][31][32][33][34][35].…”
Section: Significance Of the Studymentioning
confidence: 99%